Casting and hot isostatic pressing of silicon carbide particulate reinforced alumimium alloy based composites - Xu, Zi Ming. (2009)
SiC particulate reinforced composites based on two aluminium alloys (A3 56 and 6061) were produced by conventional stir-casting technique in the present study. A two-step mixing method was used to disperse the SiC particles in the aluminium alloys and was found to improve the wetting and distribution properties of the particles. The SiC particles were observed to be accumulated predominantly in the interdendritic regions, and a thermal lag model is proposed to explain the concentration of particles. It was found that the SiC particles acted as substrates for heterogeneous nucleation of Si crystals in Al-Si/SiC composites. Two Duralcan cast composites (F3S.10S and F3S.20S) were hot isostatically pressed for a fixed length of time but at various pressures (in the range 100-150 MPa) and temperatures (in the range 450-550 °C). It was found that the HEP treatment increased ductility at the expense of strength for the composites studied. Quantitative image analysis showed that the HIP treatment reduced the porosity levels of the as-cast composites significantly. The improvement of ductility was attributed to the reduction of porosity levels. It is of interest to observe that increasing HEP temperature is more effective than increasing HEP pressure in terms of improvement of strength and ductility. The fracture behaviour was found to be heavily affected by the matrix properties, a soften matrix will result in a less cleavage of the SiC particles. Compression testing of pre-polished specimens revealed that the slip line generation was confined to a localized region. It was found that microcracks initiated mainly from cracking of Si particles, or from debonding in Si-Al interfaces, or from debonding in Si-SiC interfaces. It is believed that the weaker interfacial strength of Si-Al matrix interface will influence the overall properties of the cast Al-Si/SiC composites.